SOURCE, COMPOSITION AND DISTRIBUTION OF THE FLUID IN THE KURILE MANTLE WEDGE: CONSTRAINTS FROM ACROSS-ARC VARIATIONS OF B/NB AND B ISOTOPES - Ishikawa T.; Tera F. (My University, 1997)
B and Nb concentrations and B isotope composition were determined for lavas covering the entire length of the Kurile arc. B/Nb and δ11B of these lavas show clear across-arc variations in which both are highest at the trench side and continuously decrease as the slab depth increases. B/Nb in the volcanic front lavas (8–25) is significantly higher than those of MORB and OIB, indicating that the mantle wedge is extensively metasomatized by B-rich fluid derived from the subducting slab. The frontal δ11B values are also out of the range of MORB and OIB, and systematic difference exists between Northern Kurile (NK: +5.4±0.5‰) and Central and Southern Kurile (CSK: +4.3±0.3‰). However, these two parameters approach or coincide with mantle values at the most back-arc side. The δ11B and 87Sr/86Sr linearly correlate with Nb/B, suggesting control by simple mixing of two isotopically homogeneous components; that is, slab-derived fluid and mantle wedge. The estimated δ11B and 87Sr/86Sr of the fluid are +7.0±0.6‰ and 0.70326±0.00005 for NK, and +6.3±0.3‰ and >0.7033 for CSK, respectively. These fluid compositions are consistent with a source constituted by >95% altered oceanic crust and <5% oceanic sediment, with the slight difference between NK and CSK resulting from the different lithologies of subducting sediments. The mantle wedge beneath the Kurile arc has B, Sr and Nd isotope compositions identical with MORB but shows significantly higher B/Nb. The above trends bear a close resemblance to those observed in the Izu arc, strongly suggesting their universality in the arc system. The across-arc decline of B/Nb observed both in Kurile and Izu implies that the fluid flux from the slab continuously decreases as the slab depth increases. However, this relates only to a final stage of slab dehydration since most of the volatile components are lost at the fore-arc region. In contrast to B, K is uniformly enriched across the arc. This requires control by a K-bearing mineral phase either in the slab (phengite) or the mantle wedge (phlogopite), although such a mineral is responsible for only a small part of the whole fluid transport.